From Revolutionary History to Cultural Tourism: The Historical Connotation and Cultural Tourism Development Strategies of Zhuokeji Red Cultural Heritage (Journal of humanities and social sciences exploratio, 2025)
As one of the significant revolutionary sites where the Red Army operated after entering northwestern Sichuan during the Long March, Zhuokeji preserves a wealth of distinctive red cultural heritage. This heritage not only documents the historical process of contact, communication, and solidarity between the Red Army and ethnic minorities but also bears witness to the unwavering revolutionary spirit under extremely challenging conditions. With the advancement of cultural confidence and the rural revitalization strategy, the red cultural heritage in Zhuokeji has increasingly become a vital element for local cultural and tourism development. However, issues such as simplistic cultural interpretation, homogenized tourism products, inadequate activation of resources, and weak capacity for transforming cultural value persist during the development process. Based on categorizing the types and historical connotations of Zhuokeji’s red cultural heritage and aligning with the development trends of cultural and tourism integration in ethnic regions, this paper proposes systematic strategies from multiple perspectives. The study argues that Zhuokeji’s red cultural heritage serves not only as an important medium for revolutionary history education but also as a cultural resource for fostering a sense of community for the Chinese nation in ethnic regions. Therefore, efforts should be made to promote the integration of culture and tourism on the basis of scientific conservation, enabling it to become a significant force for narrating China’s stories effectively, promoting ethnic unity, and driving local revitalization in the new era.
Keywords: Zhuokeji; Red cultural heritage; Long march; Ethnic regions; Cultural tourism